2018
DOI: 10.1177/2325967118805385
|View full text |Cite
|
Sign up to set email alerts
|

Nonarthroplasty Surgical Treatment Options for Massive, Irreparable Rotator Cuff Tears

Abstract: Massive, irreparable rotator cuff tears (MIRCTs) provide a significant dilemma for orthopaedic surgeons. One treatment option for MIRCTs is reverse total shoulder arthroplasty. However, other methods of treating these massive tears have been developed. A search of the current literature on nonoperative management, arthroscopic debridement, partial repair, superior capsular reconstruction (SCR), graft interposition, balloon spacer arthroplasty, trapezius transfer, and latissimus dorsi transfer for MIRCTs was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 68 publications
0
29
0
3
Order By: Relevance
“…These include nonoperative management with structured physical therapy, partial RCR, isolated debridement and acromioplasty, long head of the biceps tenotomy, superior capsular reconstruction, graft interposition, balloon spacer arthroplasty, tendon transfers, and RTSA. 3,32,39 A full systematic review of all treatment options is beyond the scope of this article, but we believe that this systematic review helps inform the clinician that RCR in this age group can be successful for the appropriately selected patient.…”
Section: Discussionmentioning
confidence: 99%
“…These include nonoperative management with structured physical therapy, partial RCR, isolated debridement and acromioplasty, long head of the biceps tenotomy, superior capsular reconstruction, graft interposition, balloon spacer arthroplasty, tendon transfers, and RTSA. 3,32,39 A full systematic review of all treatment options is beyond the scope of this article, but we believe that this systematic review helps inform the clinician that RCR in this age group can be successful for the appropriately selected patient.…”
Section: Discussionmentioning
confidence: 99%
“…Partial repair was first described by Burkhart et al, 8 and several studies found a statistically significant improvement in functional outcome scores versus preoperatively. 9 However, Burkhart and Hartzler 10 found that pseudoparalysis can be more reliably reversed after superior capsular reconstruction (90%) than with partial repair (44%).…”
Section: Discussionmentioning
confidence: 99%
“…Tendon transfer is a good option for irreparable failed rotator cuff repair patients. Muscles commonly used for tendon transfer include latissimus dorsi (LD), pectoralis major (PM), and lower trapezius (LT) [73,74]. Since the LD transfer is intended to restore the posterior force-couple of the shoulder, LD transfer requires consideration in rupture of the rotator cuff, including posterior part of supraspinatus and infraspinatus and teres minor.…”
Section: Tendon Transfer: Latissimus Dorsimentioning
confidence: 99%